Old photograph album - 1950s - Bain, Jack (1955)
This old black and white album from the 1950s displays pictures taken all over mostly Queensland in the 1950s. Jack Bain worked for the Bank of Australasia and worked in many branches over his career. Some images are of these banks. Also included are local landmarks (both manmade and natural), famliy events, other buildings, images of friends, beach and picnic trips and other things of interest to Jack. Individual photographs will be scanned from this album and added to the collection in the appropriate geographic locations in the future.